Midwifery Counseling Strategies to Prevent Unintended Pregnancies among Young Mothers - Sitti Umrah, Andi; Dahlan, Andi Kasrida; Juliani, Juliani (Journal of Applied Nursing and Health, 2025)
Background: Unintended pregnancy (UP) among young mothers is a pressing reproductive health issue that has drawn widespread attention globally. This phenomenon is deeply concerning as it poses serious physical and psychological risks, particularly for young mothers, and also endangers the well-being of their newborns. This study aims to analyze the effectiveness of behavior-based midwifery counselling interventions in preventing unintended pregnancies among young mothers. Methods: This pre-experimental pre-post-test study involved 102 randomly selected young mothers under 20 years old who were at risk of unintended pregnancy and not using contraception. The sample size was calculated using General Power Analysis. Data were collected using validated questionnaires and observation sheets. The intervention consisted of six weekly counseling sessions covering unintended pregnancy, contraception, reproductive health, attitude change, behavioral decision-making, and reinforcement. The study followed CONSORT guidelines for non-randomized trials and received ethical approval from Universitas Muhammadiyah Palopo (Protocol No. 045/KEP/III.3.AU/F/2024). Data were analyzed using the Wilcoxon test in SPSS v28.. Results: The findings revealed significant improvements in knowledge (from 33 to 83), attitudes (from 40 to 80), and behavior (from 30 to 70) after the intervention. Wilcoxon test results indicated statistically significant differences before and after the intervention across all three variables (ρ < 0.001; < α = 0.05). Conclusion: Behavior-based midwifery counselling is effective in preventing unintended pregnancy among young mothers. This study recommends implementing structured counselling programs and midwife training for more effective prevention strategies.